Endoxifen, a New Treatment Option for Mania: A Double‐Blind, Active‐Controlled Trial Demonstrates the Antimanic Efficacy of Endoxifen. Issue 5 (27th June 2016) - Ahmad, A; Sheikh, S; Shah, T; Reddy, MS; Prasad, BSV; Verma, KK; Chandrakant, BB; Paithankar, M; Kale, P; Solanki, RV; Patel, R; Barkate, H; et al.
Abstract : The protein kinase C (PKC) signaling system plays a role in mood disorders and PKC inhibitors such as endoxifen may be an innovative medicine for bipolar disorder (BP) patients. In this study we show for the first time the antimanic properties of endoxifen in patients with bipolar I disorder (BPD I) with current manic or mixed episode. In a double‐blind, active‐controlled study, 84 subjects with BPD I were randomly assigned to receive endoxifen (4 mg/day or 8 mg/day) or divalproex in a 2:1 ratio. Patients orally administered 4 mg/day or 8 mg/day endoxifen showed significant improvement in mania assessed by the Young Mania Rating Scale as early as 4 days. The effect remained significant throughout the 21‐day period. At study end point, response rates were 44.44% and 64.29% at 4 mg/day and 8 mg/day of endoxifen treatment, respectively. Thus, endoxifen has been shown as a promising novel antimanic or mood stabilizing agent.